P263 Does the use of lactate improve the CURB-65 score in community acquired pneumonia patients admitted to a district general hospital?. (15th November 2016) - Nicholson, TW; Connaire, S; Kronsten, V; Black, S; Park, JES
Abstract : Community acquired pneumonia (CAP) is a leading cause of admission and mortality. CURB-65 is the traditional risk stratification score. This can under predict severity in the young and does not predict requirement for higher level care. Combining CURB-65 with lactate can improve this. 1 We reviewed CAP admissions over one month to determine if lactate improved risk stratification. CAP patients were identified via coding. Authors reviewed admission chest radiographs and reports to confirm CAP. CURB-65 score was calculated from the electronic patient record (EPR), and electronic discharge letters. Lactate values were identified from Emergency Department documents scanned into EPR. Accuracy of coding and mortality in a wrongly coded group was a secondary measurement. A LAC–CURB score of low, medium or high was allocated. 138 episodes of CAP were coded. 89 were confirmed CAP. Mean age was 71.2 yrs (21–98). CURB-65 score was available in 87. 45 scored CURB-65 0–1 with 2 deaths (4.4%). 24 were CURB-65 2, with 8 deaths (33.3%) and 6 of 18 CURB-65 3–5 patients died (33.3%). A lactate value was available in 52. 16 had a low LAC-CURB score with 0 deaths and 1 ICU admission. 23 had a medium score, with 3 deaths (13%) and 2 ICU admissions. 13 had a high LAC-CURB score, with 4 deaths (31%) and 1 ICU admission. In 4 patients it was the lactate value that increased the risk category from a medium CURB-65 score to a High LAC-CURB score. All 4 were admitted to ICU, with 2 deaths. Length of stay did not alter significantly with CURB-65 or LAC-CURB, but increased with severity. Diagnoses were available in 45 of the 49 patients coded incorrectly as CAP with a 17.78% mortality rate, identical to the CAP group. Mortality was higher for medium and high CURB-65 patients, but a difference between them was only seen when the LAC-CURB score was applied. A high lactate identified patients in the medium CURB-65 group who died or required higher level care. Patients wrongly coded as CAP also have a high mortality. Reference: Chen YX. Thorax 2015;70 (5).